Habitat use and characterization of the seascape exploited by wintering adult and juvenile Southern Giant Petrels from Patagonia - Blanco, Gabriela Silvina (2015)
The characterization of the seascape used by top predators helps to understand the functioning of marine systems. The main goals of this study were to 1) analyze habitat use and at-sea movements of adult and first year juvenile southern giant petrels (SGP, Macronectes giganteus) during the austral winter, and 2) to characterize the oceanographic and biological features of their marine environment.